Discovery of a radio relic in the low mass, merging galaxy cluster PLCK G200.9−28.2 . Issue 1 (12th August 2017) - Kale, Ruta; Wik, Daniel R.; Giacintucci, Simona; Venturi, Tiziana; Brunetti, Gianfranco; Cassano, Rossella; Dallacasa, Daniele; de Gasperin, Francesco
Abstract: Radio relics at the peripheries of galaxy clusters are tracers of the elusive cluster merger shocks. We report the discovery of a single radio relic in the galaxy cluster PLCK G200.9−28.2  ( z  = 0.22, M 500  = 2.7 ± 0.2 × 10 14  M⊙ ) using the Giant Metrewave Radio Telescope at 235 and 610 MHz and the Karl G. Jansky Very Large Array at 1500 MHz. The relic has a size of ∼1 × 0.28 Mpc, an arc-like morphology and is located at 0.9 Mpc from the X-ray brightness peak in the cluster. The integrated spectral index of the relic is 1.21 ± 0.15. The spectral index map between 235 and 610 MHz shows steepening from the outer to the inner edge of the relic in line with the expectation from a cluster merger shock. Under the assumption of diffusive shock acceleration, the radio spectral index implies a Mach number of 3.3 ± 1.8 for the shock. The analysis of archival XMM–Newton   data shows that PLCK G200.9−28.2  consists of a northern brighter sub-cluster, and a southern sub-cluster in a state of merger. This cluster has the lowest mass amongst the clusters hosting single radio relics. The position of the Planck   Sunyaev–Ze'ldovich effect in this cluster is offset by 700 kpc from the X-ray peak in the direction of the radio relic, suggests a physical origin for the offset. Such large offsets in low mass clusters can be a useful tool to select disturbed clusters and to study the state of merger.